The First Age of Reptiles? Comparing Reptile and Synapsid Diversity, and the Influence of Lagerstätten, During the Carboniferous and Early Permian - Brocklehurst, Neil (Frontiers in Ecology and Evolution, 2021)
Terrestrial ecosystems during the Pennsylvanian (late Carboniferous) and Cisuralian (early Permian) are usually described in the literature as being dominated by synapsids, the mammal-line amniotes. The pelycosaurs (a paraphyletic grouping of synapsid families) have been considered more speciose, abundant, and ecologically diverse than contemporary reptile-line amniotes. However, this dominance has never been subjected to quantitative testing accounting for sampling bias. Moreover, in recent years the amniote phylogeny has undergone numerous revisions, with suggestions that varanopids and recumbirostran microsaurs fall within reptiles, and that diadectomorphs may be pelycosaurian-grade synapsids. An examination of local species richness (alpha diversity) of synapsids and reptiles during the Pennsylvanian and Cisuralian at different spatial scales shows that these taxonomic revisions have substantial impacts on relative diversity patterns of synapsids and reptiles. Synapsids are only found to be consistently more diverse through the early Permian when using the ‘traditional’ taxonomy. The recent taxonomic updates produce diversity estimates where reptile diversity is consistent with, or in some cases higher than that of synapsids. Moreover, biases in preservation may affect patterns. Where preservation favours smaller vertebrates, e.g. Richards Spur, South Grandfield, reptiles overwhelmingly dominate. If smaller vertebrates are expected to make up the bulk of amniote diversity, as they do in the present day, such lagerstätten may be more representative of true diversity patterns. Therefore, the dominance of pelycosaurs during this interval should be reconsidered, and this interval may be considered the First Age of Reptiles.